EVALUASI REAKSI TINGKAT KEPUASAN PESERTA DIKLAT MEMBATIK DI SANGGAR BATIK CIKADU TANJUNG LESUNG - Minhatul Ma’arif; Rizal Fauzi; Irma Murti Kusuma Anggara (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to evaluate the reaction of PG-PAUD students’ satisfaction level to the training program organized by Sanggar Batik Cikadu Tanjung Lesung. This approach used a qualitative approach by adopting kirkpatrick evaluation model at level 1. Respondents to this study were 25 people who had participated in the training. The results of the study obtained that 60% of students dissatisfied with the material provided, 40% of students were dissatisfied with the implementation of the material due to delays in implementation time, all students were satisfied with the facilities and infrastructure of the training and all students were satisfied with the performance of the instructor. Thus, this study concluded that although batik instructors had a reliable ability in facilitating student learning and the infrastructure facilities provided greatly support the implementation of training but they were not able to overcome students’ learning problems because the material presented was not in accordance with the needs of the participants of the training. In fact, the training through the art of batik was expected to be able to bridge students’ problems in creativity and blessing courses in order to build creativity and talent of students in the art of batik. Unfortunately, student did not like the art of polishing so that the results of the questionnaire obtained showed that only 40% of students were interested in the art of painting.